Reciprocal Teaching Strategy on Students’ Reading Comprehension of Descriptive Text - Utama, I Made Permadi; Hidayatullah, Heri (International Journal of English Education and Linguistics (IJoEEL), 2025)
This study investigates the effectiveness of the Reciprocal Teaching strategy in improving the reading comprehension of descriptive texts among first-semester students in the English Language Program at FBMB UNDIKMA. Grounded in Vygotsky’s social constructivist theory, Reciprocal Teaching encourages active student engagement through four key strategies: predicting, questioning, clarifying, and summarizing. Employing a quasi-experimental design with a posttest-only control group, the research involved 37 students and utilized pretest and posttest assessments to measure comprehension gains. The findings revealed a significant improvement in students' reading scores following the intervention, as evidenced by a mean score increase from 66.84 to 76.89 and a statistically significant p-value of 0.000. These results suggest that the Reciprocal Teaching strategy is a highly effective approach for enhancing students’ understanding of descriptive texts, promoting not only improved academic outcomes but also greater engagement and metacognitive awareness. The study underscores the potential of Reciprocal Teaching as a practical instructional method, while also noting challenges such as time constraints and classroom management. Future research should explore broader applications of the strategy across diverse text types and educational settings.